Long-term outcome of children with oesophageal atresia type III. Issue 9 (29th June 2012) - Legrand, Céline; Michaud, Laurent; Salleron, Julia; Neut, Dorothée; Sfeir, Rony; Thumerelle, Caroline; Bonnevalle, Michel; Turck, Dominique; Gottrand, Frederic
Abstract : Objective: The aim of this study was to evaluate the outcome of patients with oesophageal atresia type III (EA), focusing on the presence of late sequelae and quality of life. Methods: This was a retrospective case ascertainment followed by clinical assessment of patients. The study parameters included the patients' demographic characteristics, associated abnormalities, presence of gastro-oesophageal reflux disease (GERD) and digestive or respiratory symptoms, results of a clinical examination to evaluate nutritional status, spirometry results and quality of life assessed using the PedsQL 4.0 questionnaire. Results: Of 81 patients with EA type III treated in our institution over a 10-year period, 57 (mean age 13.3 (SE 2.8) years) participated in the study. 39% of the patients underwent fundoplication and 46% presented with anastomotic stenosis requiring dilation. 75% of patients had normal nutritional status (16% were obese, 9% were undernourished). Only 19% of participants had no digestive symptoms; 61% had dysphagia and 35% had symptoms of GERD at the last follow-up. The main respiratory symptoms were chronic cough (19%) and dyspnoea on exertion (37%). Only 37% of patients had no respiratory symptoms. Spirometry showed that 50% of patients had proximal obstruction and/or pulmonary distension, and 11% had restriction syndrome. Their quality of life was good but was lower than in healthy controls (80 vs 84, p<0.05) and lower in patients born prematurely, with symptoms of GERD and with a barky cough. Conclusion: The high frequency of late sequelae in EA type III justifies regular and multidisciplinary follow-up through to adulthood.